Diagnostic Approach and Treatment Regimens in Adult Patients Suffering from Antibody- mediated or Paraneoplastic Encephalitis - Macher, Stefan; Bsteh, Gabriel; Berger, Thomas; Höftberger, Romana (Current Pharmaceutical Design, 2022)
Identification of patients with antibody-mediated encephalitis poses a diagnostic challenge, and any delay in that aspect will increase the interval until the initiation of immunotherapy and may negatively affect the patient´s clinical outcome. Within this review, we focus on therapeutic strategies in antibody-mediated encephalitis and propose how to proceed with patients who are suspected of having encephalitis of unknown origin. We further briefly outline differences in the treatment of paraneoplastic and antibody-mediated encephalitis according to its pathomechanisms.
Keywords: regimens